2020
DOI: 10.3389/fnins.2020.00680
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation at 20 Hz Improves Depression-Like Behaviors and Down-Regulates the Hyperactivity of HPA Axis in Chronic Unpredictable Mild Stress Model Rats

Abstract: Transcutaneous auricular vagus nerve stimulation (taVNS) has gained growing interest as a non-invasive and non-pharmacologic treatment option in various neurological and psychiatric disorders. Animal experiments and clinical trials confirm that taVNS at the auricular concha region has beneficial effects on depression. However, stimulation frequencies are selected empirically, and there is no evidence showing that any frequency is superior to the others. This study explores antidepressant-like effects of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…In this study, we evaluated depressive-like behavior in CUMS model rats by using the three behavioral methods described above. We come to the conclusion that taVNS can alleviate the depression-like behaviors induced by CUMS in rats, which is to some extent consistent with our previous clinical studies [ 47 ]. It was found that CUMS significantly decreased the exploration and locomotion ability of rats in OFT, and decreased the immobility time as well as the percentage of sucrose preference in SPT.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we evaluated depressive-like behavior in CUMS model rats by using the three behavioral methods described above. We come to the conclusion that taVNS can alleviate the depression-like behaviors induced by CUMS in rats, which is to some extent consistent with our previous clinical studies [ 47 ]. It was found that CUMS significantly decreased the exploration and locomotion ability of rats in OFT, and decreased the immobility time as well as the percentage of sucrose preference in SPT.…”
Section: Discussionsupporting
confidence: 91%
“…taVNS, as a non-invasive intervention, has beneficial effects on a wide range of neurological, psychiatric, and medical conditions based on clinical observations. Animal experiments and clinical trials have demonstrated that taVNS in the auricular concha region elicits therapeutic effects on depression symptoms (37,38). Moreover, VNS was approved by the United States Food and Drug Administration in 2005 for treating chronic refractory depression (39).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, its dysfunction induced by surgery, anesthesia, anxiety, and pain often results in endocrine disorders and immunosuppression ( Kim, 2017 ; Tafet and Nemeroff, 2020 ). With the continuation of HPA axis hyperactivity, diseases such as diabetes ( Miranda et al, 2016 ), high blood pressure ( Muraca et al, 2021 ), and depression ( Li et al, 2020 ) will inevitably appear. To simulate HPA axis hyperactivity in clinical situations, the HT mouse model was employed in the present study.…”
Section: Discussionmentioning
confidence: 99%